What influences new graduate nurses' core competencies transformation to clinical in China? A cross-sectional study. (May 2021) - Xie, Jianfei; Wang, Lu; Wang, Sha; Duan, Yinglong; Wang, Kewei; Zhong, Zhuqing; Yan, Jin; Ding, Siqing; Li, Lijun; Cheng, Andy S.K.
Abstract: Background: The core competencies of new graduate nurses (NGNs) have significant health outcomes in the clinical environment. However, these nurses experience a theory-practice gap, which creates a barrier in the transition process when they first enter the clinical workplace. Objective: To understand the general overview of the transition of the core competencies of NGNs to clinical practice in China and the influencing factors. Design and setting: A cross-sectional study design consisting of a multi-stratified grounded random sample from 31 hospitals in seven regions nationwide. Participants: 2400 NGNs were recruited by email. Methods: The Competencies Inventory for Registered Nurse (CIRN) was applied to evaluate NGNs' core competencies. Results: NGNs performed best on leadership and worst on critical thinking or research aptitude. Core competencies were predicted by depressive symptoms, worked for two-three years, having a nurse-in-charge title, professional values, department, happiness, etc. Besides, the preceptor program also has significant to core competencies. Conclusion: The average level of Chinese NGNs' core competencies was at a moderate level, which wasn't well optimized. It is recommended to adopt appropriate interventions to support NGNs. With an increase in work years and the accumulation of more work experience, the corresponding core competencies of NGNs will also improve. Preceptor institutions, limiting first-degree recruitment, and early ICU or operating room department rotations can be carried out by nursing educators to improve core competencies.